The Relationship between Religiosity and Resilience of Covid-19 Survivors - Diyan Putri Wahyuningrum; Ratna Yunita Setiyani (Journal of Health Sciences and Medical Development, 2022)
The Covid-19 pandemic has spread around the globe, including in Indonesia. The Special Region of Yogyakarta is one of the areas listed in the red zone. Covid-19 has had a wide range of effects on survivors' physical and mental health. According to research, survivors feel anxiety, trauma, and even depression. Resilience is one way for survivors to rise above difficult circumstances. Experts believe that religiosity is one factor that promotes the development of resilience. The study aims to determine the correlation between religiosity and resilience in Covid-19 survivors. This research was quantitative research with the correlational method. The research data were collected using two scales, namely the religiosity scale and the CD-RISC 25 resilience scale. The respondents of this study consisted of 121 subjects from all regencies and municipalities in the Special Region of Yogyakarta, Indonesia which were taken by random sampling technique. The study found a positive correlation between religiosity and resilience in Covid-19 survivors. The correlation coefficient is 0.621, indicating that the stronger the religiosity, the higher the resilience of Covid-19 survivors. Moreover, the effective contribution of the religiosity variable to resilience was 38.5%, as indicated by the determinant coefficient equal to 0.385.